Preparation method of photocatalytic degradation material for treating cefradine-containing wastewater
An efficient photocatalytic degradation material was prepared by loading poly[N-mercapto-3-butylamidopyrrole-2,5-bis(p-methylstyrene)] on the surface of nickel foam matrix and assembling Bi2GdO3SeI nanocrystals. , which solves the problem of low degradation efficiency of cephradine sewage in the existing technology and achieves efficient sewage treatment.
Patent Information
- Application Number
- CN202411466589.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing photocatalytic materials are not efficient in degrading cefoladin sewage, have a low removal rate, and are difficult to meet the requirements of environmental protection and industrial rapid treatment.
By synthesizing N-mercapto-3-butylamidopyrrole and Bi2GdO3SeI nanocrystals, and loading poly[N-mercapto-3-butyrylamidopyrrole-2,5-bis(p-methylstyrene) on the surface of nickel foam matrix ] and assembled Bi2GdO3SeI nanocrystals to prepare photocatalytic degradation materials with outstanding UV and visible light degradation properties of cephradine.
Efficient degradation of cephradine sewage has been achieved, with ultraviolet and visible light degradation rates reaching over 96% and 91% respectively, significantly improving the efficiency and removal rate of sewage treatment.
Smart Images

Figure CN119346169A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocatalytic degradation materials for sewage treatment, in particular to a method for preparing a foamed nickel-based composite material for photocatalytically degrading p-nitrophenol. Background Art
[0002] Cefradine is a β-lactam antibiotic belonging to the cephalosporin class of antibacterial drugs. It inhibits and kills bacteria by interfering with and inhibiting bacterial protein synthesis, cell wall formation, and DNA replication. At present, the production of cephalosporin antibiotics accounts for more than 60% of the total global antibiotic production, and the use of cephalosporin antibiotics in my country accounts for more than half of the total antibiotic use.
[0003] After humans and animals use cephalosporin antibiotics, these substances are excreted into the environment, including pharmaceutical wastewater, pesticides and feed additives, becoming an important source of wastewater containing cephalosporin. When untreated sewage enters the environment, it can cause bacteria to develop drug resistance and cause chronic poisoning to microorganisms, algae and fish in the water. At the same time, long-term drinking of contaminated water or ingestion of cephalosporin through the food chain may lead to digestive system flora imbalance and a surge in drug-resistant bacteria. In addition, cephalosporin may interfere with DNA replication and cell division, and is carcinogenic, teratogenic and mutagenic.
[0004] Since it is difficult for organisms to effectively degrade cefradine, cefradine in water bodies is mainly degraded by direct photolysis, but it is difficult to completely remove it, posing a serious threat to human health and the ecological environment. Traditional flocculation, sedimentation and membrane separation wastewater treatment technologies cannot effectively degrade cefradine. Photocatalytic degradation technology uses light to irradiate catalytic materials to degrade pollutants into harmless carbon dioxide and water, and is an ideal green and environmentally friendly method for treating wastewater containing cefradine. However, the photocatalytic materials prepared by the prior art are not efficient in degrading cefradine, and the removal rate is low, which makes it difficult to meet the requirements of environmental protection and rapid industrial processing. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a photocatalytic degradation material for treating wastewater containing cephradine. The photocatalytic degradation material prepared by the method has outstanding cephradine ultraviolet and visible light degradation performance.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] The present invention provides a method for preparing a photocatalytic degradation material for treating wastewater containing cefuroxime, comprising the following steps:
[0008] Step [1] synthesizing N-mercapto-3-butyrylaminopyrrole;
[0009] Step [2] Preparation of Bi 2 GDj 3 SeI nanocrystals;
[0010] Step [3] Loading poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] on the surface of nickel foam substrate and assembling Bi 2 GDj 3 SeI nanocrystals.
[0011] Preferably, the step [1] specifically includes the following operations:
[0012] Add mercaptopropionic acid and pyrrole into ethanol and mix to form a synthetic liquid A; add butanamide and ferric chloride into deionized water and mix to form a synthetic liquid B; add a certain amount of synthetic liquid A into the synthetic liquid B, react at room temperature for 4-6 hours, and obtain an N-mercapto-3-butyrylamide pyrrole product solution.
[0013] Preferably, the concentration of mercaptopropionic acid in the synthetic liquid A is 80 mL / L-100 mL / L, and the concentration of pyrrole is 190 mL / L-220 mL / L; the concentration of butanamide in the synthetic liquid B is 110 g / L-140 g / L, and the concentration of ferric chloride is 40 g / L-70 g / L; the volume ratio between the synthetic liquid A and the synthetic liquid B is 3-5:1-2.
[0014] Preferably, the step [2] specifically includes the following operations:
[0015] b1. Gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide were added to deionized water and mixed to form a reaction solution A; stirred at room temperature for 5 to 7 hours until a solid phase was precipitated, the solid phase was filtered with filter paper, and dried at 40-60 ° C for 3 to 4 hours to obtain a GdSeOI precursor;
[0016] b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor to deionized water, mix to obtain a reaction solution B, heat to 120-150 ° C, react for 8-12 hours, then cool to room temperature, filter and dry at 40-60 ° C for 5 to 7 hours to obtain Bi 2 GDj 3 SeI nanocrystals.
[0017] Preferably, in step b1, the concentration of gadolinium nitrate in reaction solution A is 50 g / L-90 g / L, the concentration of cerium trichloride is 110 g / L-140 g / L, the concentration of tetrabutylammonium iodide is 40 g / L-80 g / L, and the concentration of sodium iodide is 20 g / L-60 g / L.
[0018] Preferably, in step b2, the amount of bismuth nitrate added to each liter of reaction solution B is 130 g-170 g, the amount of ammonium cerium nitrate added is 20 g-40 g, and the amount of GdSeOI precursor added is 210 g-230 g.
[0019] Preferably, the step [3] specifically includes the following operations:
[0020] c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent, 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi 2 GDj 3 SeI nanocrystals are added into the mixed solvent to form an additive solution;
[0021] c2. Immerse the nickel foam in the N-mercapto-3-butyrylamide pyrrole product solution for 3-10 minutes at room temperature, then add a certain amount of the additive solution, heat to 50-70° C. in a water bath and react for 8-12 hours to complete the loading of poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] and Bi on the surface of the nickel foam. 2 GDj 3 The SeI crystals are assembled to finally obtain the photocatalytic degradation material.
[0022] Preferably, in step c1, the volume ratio of dimethyl sulfoxide to tetrahydrofuran in the mixed solvent is 1:1; the amount of 1-chloro-3-ethylbenzene added per liter of the additive solution is 140mL-190mL, the amount of dibenzoyl peroxide added is 20g-40g, and the amount of Bi 2 GDj 3 The amount of SeI nanocrystals added is 70g-90g.
[0023] Preferably, in step c2, the weight of the nickel foam immersed in each liter of the N-mercapto-3-butyrylamide pyrrole product solution is 110-130 g; and the volume ratio between the additive liquid and the N-mercapto-3-butyrylamide pyrrole product solution is 1:1.
[0024] The positive effect of the present invention is that the photocatalytic degradation material prepared by the method according to the present invention is synthesized on the surface of nickel foam poly [N-mercapto-3-butyrylamide pyrrole-2,5-di (p-methylphenylene)] and assembled Bi 2 GDj 3 SeI nanocrystals, wherein poly[N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] is formed by polymerization of N-mercapto-3-butyrylamide pyrrole substituted with N-mercapto and 3-butyrylamide and 1-chloro-3-ethylbenzene, Bi 2 GDj 3SeI crystal has a tetragonal structure and belongs to the space group P4 / nmm. 2 O 2 Poly[N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] has a narrow band gap and large π electron delocalization characteristics, and is a narrow band gap π conjugated organic compound. The N-mercapto substitution and 3-butyrylamide substitution on the pyrrole ring and the methyl substitution on the benzene ring of the organic main chain are conducive to the formation of an internal electric field in the organic complex, which can inhibit the recombination of photogenerated electrons and photogenerated holes, while Bi 2 GDj 3 SeI crystals have a unique layered structure and a narrow bandgap formed by the hybridization of bismuth electron orbitals, which give them excellent photocatalytic activity.
[0025] In conclusion, the photocatalytic degradation material prepared according to the present invention has outstanding performance of cephradine degradation under ultraviolet and visible light. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the preparation process of the photocatalytic degradation material of the present invention;
[0027] Figure 2 It is a schematic diagram of the structure of the photocatalytic degradation material of the present invention;
[0028] Figure 3 The photocatalytic degradation rate of cephradine in treating simulated cephradine-containing wastewater when the usage amount of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention is 40 g;
[0029] Figure 4 The photocatalytic degradation rate of cephradine in treating simulated cephradine-containing wastewater when the usage amount of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention is 20 g. DETAILED DESCRIPTION
[0030] Reference Figure 1 The present invention provides a method for preparing a photocatalytic degradation material for treating wastewater containing cephradine, comprising the following steps:
[0031] Step [1] synthesizing N-mercapto-3-butyrylaminopyrrole, specifically comprises the following operations:
[0032] Add mercaptopropionic acid and pyrrole into ethanol and mix to form a synthetic liquid A with a mercaptopropionic acid concentration of 80 mL / L-100 mL / L and a pyrrole concentration of 190 mL / L-220 mL / L; add butanamide and ferric chloride into deionized water and mix to form a synthetic liquid B with a butanamide concentration of 110 g / L-140 g / L and a ferric chloride concentration of 40 g / L-70 g / L; add a certain amount of synthetic liquid A into the synthetic liquid B (the volume ratio between the synthetic liquid A and the synthetic liquid B is 3-5:1-2), react at room temperature for 4-6 hours, and obtain an N-mercapto-3-butyrylamide pyrrole product solution.
[0033] Step [2] Preparation of Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0034] b1. Add gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide to deionized water to form a reaction solution A having a gadolinium nitrate concentration of 50 g / L-90 g / L, a cerium trichloride concentration of 110 g / L-140 g / L, a tetrabutylammonium iodide concentration of 40 g / L-80 g / L, and a sodium iodide concentration of 20 g / L-60 g / L; stir well at room temperature for 5 to 7 hours until a solid phase precipitates, filter the solid phase with filter paper, and dry at 40-60 ° C for 3 to 4 hours to obtain a GdSeOI precursor;
[0035] b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor to deionized water, mix to obtain a reaction solution B (the amount of bismuth nitrate added to each liter of reaction solution B is 130g-170g, the amount of ammonium cerium nitrate added is 20g-40g, and the amount of GdSeOI precursor added is 210g-230g), heat to 120-150°C, react for 8-12 hours, then cool to room temperature, filter and dry at 40-60°C for 5 to 7 hours to obtain Bi 2 GDj 3 SeI nanocrystals.
[0036] Step [3] Loading poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] on the surface of nickel foam substrate and assembling Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0037] c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent (the volume ratio between dimethyl sulfoxide and tetrahydrofuran is 1:1), 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi 2 GDj 3SeI nanocrystals are added to the mixed solvent to form an additive solution (the amount of 1-chloro-3-ethylbenzene added per liter of the additive solution is 140 mL-190 mL, the amount of dibenzoyl peroxide added is 20 g-40 g, and the amount of Bi 2 GDj 3 The amount of SeI nanocrystals added is 70g-90g);
[0038] c2. Immersing the nickel foam in the N-mercapto-3-butyrylamide pyrrole product solution (the weight of the nickel foam immersed in each liter of the N-mercapto-3-butyrylamide pyrrole product solution is 110-130 g), immersing for 3-10 minutes at room temperature, then adding a certain amount of the additive solution (the volume ratio between the additive solution and the N-mercapto-3-butyrylamide pyrrole product solution is 1:1), heating in a water bath to 50-70° C. and reacting for 8-12 hours to complete the loading of poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] and Bi on the surface of the nickel foam 2 GDj 3 The assembly of SeI crystals finally obtains the photocatalytic degradation material, and its microstructure is shown in the figure below. Figure 2 Wherein, the reaction formula for the polymerization reaction of N-mercapto-3-butyrylamide pyrrole and 1-chloro-3-ethylbenzene to form poly[N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] is:
[0039]
[0040] The preferred embodiments of the present invention are described below by way of example.
[0041] Example 1
[0042] Preferred embodiment 1 of the present invention provides a method for preparing a photocatalytic degradation material for treating wastewater containing cefuroxime, comprising the following steps:
[0043] Step [1] synthesizing N-mercapto-3-butyrylaminopyrrole, specifically comprises the following operations:
[0044] Add mercaptopropionic acid and pyrrole to ethanol and mix to form a synthetic liquid A with a mercaptopropionic acid concentration of 90 mL / L and a pyrrole concentration of 210 mL / L; add butanamide and ferric chloride to deionized water and mix to form a synthetic liquid B with a butanamide concentration of 130 g / L and a ferric chloride concentration of 60 g / L; add a certain amount of synthetic liquid A to the synthetic liquid B (the volume ratio between the synthetic liquid A and the synthetic liquid B is 4:1), react at room temperature for 5 hours, and obtain an N-mercapto-3-butyrylamide pyrrole product solution.
[0045] Step [2] Preparation of Bi 2 GDj 3SeI nanocrystals, specifically including the following operations:
[0046] b1. Gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide were added to deionized water to form a reaction solution A having a gadolinium nitrate concentration of 80 g / L, a cerium trichloride concentration of 120 g / L, a tetrabutylammonium iodide concentration of 70 g / L and a sodium iodide concentration of 40 g / L; the mixture was stirred at room temperature for 6 hours until a solid phase was precipitated, the solid phase was filtered with filter paper, and dried at 55 ° C for 4 hours to obtain a GdSeOI precursor;
[0047] b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor into deionized water, mix to obtain reaction solution B (150 g of bismuth nitrate, 30 g of ammonium cerium nitrate and 220 g of GdSeOI precursor per liter of reaction solution B), heat to 140°C, react for 10 hours, then cool to room temperature, filter and dry at 50°C for 6 hours to obtain Bi 2 GDj 3 SeI nanocrystals.
[0048] Step [3] Loading poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] on the surface of nickel foam substrate and assembling Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0049] c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent (the volume ratio between dimethyl sulfoxide and tetrahydrofuran is 1:1), 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi 2 GDj 3 SeI nanocrystals are added to the mixed solvent to form an additive solution (180 mL of 1-chloro-3-ethylbenzene, 30 g of dibenzoyl peroxide, and 30 g of Bi peroxide are added per liter of the additive solution). 2 GDj 3 The amount of SeI nanocrystals added was 80 g);
[0050] c2. Immersing the nickel foam in the N-mercapto-3-butyrylamide pyrrole product solution (the weight of the nickel foam immersed in each liter of the N-mercapto-3-butyrylamide pyrrole product solution is 120 g), immersing for 8 minutes at room temperature, then adding a certain amount of the additive solution (the volume ratio between the additive solution and the N-mercapto-3-butyrylamide pyrrole product solution is 1:1), heating in a water bath to 50-70° C. and reacting for 10 hours to complete the loading of poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] and Bi on the surface of the nickel foam 2 GDj 3The SeI crystals are assembled to finally obtain the photocatalytic degradation material, which is recorded as Example 1.
[0051] Comparative Example 1
[0052] This comparative example 1 provides a method for preparing a photocatalytic degradation material for treating wastewater containing cefuroxime, comprising the following steps:
[0053] Step [1] synthesizing N-mercaptopyrrole, specifically comprising the following operations:
[0054] Add mercaptopropionic acid and pyrrole into ethanol and mix to form a synthetic liquid A with a mercaptopropionic acid concentration of 90 mL / L and a pyrrole concentration of 200 mL / L; add ferric chloride into deionized water and mix to form a synthetic liquid B with a ferric chloride concentration of 50 g / L; add a certain amount of synthetic liquid A into the synthetic liquid B (the volume ratio between the synthetic liquid A and the synthetic liquid B is 4:1), react at room temperature for 5 hours, and obtain an N-mercaptopyrrole product solution.
[0055] Step [2] Preparation of Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0056] b1. Gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide were added to deionized water to form a reaction solution A having a gadolinium nitrate concentration of 60 g / L, a cerium trichloride concentration of 120 g / L, a tetrabutylammonium iodide concentration of 50 g / L and a sodium iodide concentration of 30 g / L; the mixture was stirred at room temperature for 6 hours until a solid phase was precipitated, the solid phase was filtered with filter paper, and dried at 45 ° C for 3 hours to obtain a GdSeOI precursor;
[0057] b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor into deionized water, mix to obtain reaction solution B (140 g of bismuth nitrate, 30 g of ammonium cerium nitrate and 220 g of GdSeOI precursor per liter of reaction solution B), heat to 140°C, react for 9 hours, then cool to room temperature, filter and dry at 50°C for 6 hours to obtain Bi 2 GDj 3 SeI nanocrystals.
[0058] Step [3] Loading poly [N-mercaptopyrrole-2,5-di(p-methylphenylene)] on the surface of nickel foam substrate and assembling Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0059] c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent (the volume ratio between dimethyl sulfoxide and tetrahydrofuran is 1:1), 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi2 GDj 3 SeI nanocrystals are added to the mixed solvent to form an additive solution (160 mL of 1-chloro-3-ethylbenzene, 30 g of dibenzoyl peroxide, and 30 g of Bi peroxide are added per liter of the additive solution). 2 GDj 3 The amount of SeI nanocrystals added was 80 g);
[0060] c2. Immerse the nickel foam in the N-mercaptopyrrole product solution (the weight of the nickel foam immersed in each liter of the N-mercaptopyrrole product solution is 120 g), immerse for 5 minutes at room temperature, then add a certain amount of the additive solution (the volume ratio between the additive solution and the N-mercaptopyrrole product solution is 1:1), heat to 60° C. in a water bath and react for 9 hours to complete the loading of poly[N-mercaptopyrrole-2,5-di(p-methylphenylene)] and Bi on the surface of the nickel foam. 2 GDj 3 The SeI crystals were assembled to finally obtain the photocatalytic degradation material, which is recorded as Comparative Example 1.
[0061] Comparative Example 2
[0062] This comparative example 2 provides a method for preparing a photocatalytic degradation material, comprising the following steps:
[0063] Step [1] synthesizes 3-butyrylamide pyrrole, specifically comprising the following operations:
[0064] Pyrrole is added to ethanol and mixed to form a synthetic liquid A with a pyrrole concentration of 200 mL / L; butyramide and ferric chloride are added to deionized water and mixed to form a synthetic liquid B with a butyramide concentration of 120 g / L and a ferric chloride concentration of 60 g / L; a certain amount of synthetic liquid A is added to the synthetic liquid B (the volume ratio between the synthetic liquid A and the synthetic liquid B is 5:2), and the mixture is reacted at room temperature for 4-6 hours to obtain a 3-butyramide pyrrole product solution.
[0065] Step [2] Preparation of Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0066] b1. Gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide were added to deionized water to form a reaction solution A having a gadolinium nitrate concentration of 70 g / L, a cerium trichloride concentration of 130 g / L, a tetrabutylammonium iodide concentration of 70 g / L and a sodium iodide concentration of 50 g / L; the mixture was stirred at room temperature for 6 hours until a solid phase was precipitated, the solid phase was filtered with filter paper, and dried at 50 ° C for 4 hours to obtain a GdSeOI precursor;
[0067] b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor into deionized water, mix to obtain reaction solution B (160 g of bismuth nitrate, 30 g of ammonium cerium nitrate and 220 g of GdSeOI precursor per liter of reaction solution B), heat to 140°C, react for 10 hours, then cool to room temperature, filter and dry at 50°C for 6 hours to obtain Bi 2 GDj 3 SeI nanocrystals.
[0068] Step [3] Loading poly [3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] on the surface of nickel foam substrate and assembling Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0069] c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent (the volume ratio between dimethyl sulfoxide and tetrahydrofuran is 1:1), 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi 2 GDj 3 SeI nanocrystals are added to the mixed solvent to form an additive solution (180 mL of 1-chloro-3-ethylbenzene, 30 g of dibenzoyl peroxide, and 30 g of Bi peroxide are added per liter of the additive solution). 2 GDj 3 The amount of SeI nanocrystals added was 80 g);
[0070] c2. Immerse the nickel foam in the 3-butyramide pyrrole product solution (the weight of the nickel foam immersed in each liter of the 3-butyramide pyrrole product solution is 120 g), immerse for 5 minutes at room temperature, then add a certain amount of the additive solution (the volume ratio between the additive solution and the 3-butyramide pyrrole product solution is 1:1), heat to 60° C. in a water bath and react for 10 hours to complete the loading of poly [3-butyramide pyrrole-2,5-di (p-methylphenylene)] and Bi on the surface of the nickel foam. 2 GDj 3 The SeI crystals were assembled to finally obtain the photocatalytic degradation material, which is recorded as Comparative Example 2.
[0071] In order to analyze the photocatalytic degradation removal rate of cephradine in Example 1, Comparative Example 1 and Comparative Example 2 for treating cephradine-containing sewage, cephradine was added to deionized water to prepare simulated cephradine sewage with a cephradine concentration of 20 mg / L. 100 ml of simulated cephradine sewage was poured into a beaker, 20 g and 40 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed in a beaker, and a xenon light source was used to irradiate Comparative Example 1, Comparative Example 2 and Example 1 for 14 hours under the conditions of working current 22A and working voltage 20V, ultraviolet light (λ=360nm) and visible light (λ=550nm) were used to treat the corresponding simulated cephradine sewage with photocatalytic degradation, and a comparison group under no light conditions was set at the same time. The photocatalytic degradation rate of cephradine in the simulated cephradine sewage after 80 minutes of photocatalytic degradation was calculated by high performance liquid chromatography analysis, and the results are as follows: Figure 3 and Figure 4 As shown in the figure, it can be seen that when the usage amount is 40g, the photocatalytic degradation rate of cephradine under ultraviolet light and visible light conditions in Example 1 reaches 96% and 91%, while the photocatalytic degradation rates of cephradine under ultraviolet light and visible light in Comparative Example 1 and Comparative Example 2 can only reach 64%, 52% and 42%, 34%, respectively; when the usage amount is 40g, the photocatalytic degradation rate of cephradine under ultraviolet light and visible light conditions in Example 1 can still reach 91% and 85%, respectively, while the photocatalytic degradation rates of cephradine under ultraviolet light and visible light in Comparative Example 1 and Comparative Example 2 are significantly reduced to 39%, 22% and 30%, 17%, respectively.
[0072] In summary, the photocatalytic degradation material prepared according to the present invention has outstanding cephradine ultraviolet and visible light degradation performance.
[0073] To illustrate in further detail, three additional examples are provided below.
[0074] Example 2
[0075] Preferred embodiment 2 of the present invention provides a method for preparing a photocatalytic degradation material for treating wastewater containing cefuroxime, comprising the following steps:
[0076] Step [1] synthesizing N-mercapto-3-butyrylaminopyrrole, specifically comprises the following operations:
[0077] Add mercaptopropionic acid and pyrrole into ethanol and mix to form a synthetic liquid A with a mercaptopropionic acid concentration of 80 mL / L and a pyrrole concentration of 190 mL / L; add butanamide and ferric chloride into deionized water and mix to form a synthetic liquid B with a butanamide concentration of 110 g / L and a ferric chloride concentration of 40 g / L; add a certain amount of synthetic liquid A into the synthetic liquid B (the volume ratio between the synthetic liquid A and the synthetic liquid B is 3:1), react at room temperature for 6 hours, and obtain an N-mercapto-3-butyrylamide pyrrole product solution.
[0078] Step [2] Preparation of Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0079] b1. Gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide were added to deionized water to form a reaction solution A having a gadolinium nitrate concentration of 90 g / L, a cerium trichloride concentration of 110 g / L, a tetrabutylammonium iodide concentration of 40 g / L and a sodium iodide concentration of 20 g / L; the mixture was stirred at room temperature for 7 hours until a solid phase was precipitated, the solid phase was filtered with filter paper, and dried at 60 ° C for 3 hours to obtain a GdSeOI precursor;
[0080] b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor into deionized water, mix to obtain reaction solution B (130 g of bismuth nitrate, 20 g of ammonium cerium nitrate and 210 g of GdSeOI precursor per liter of reaction solution B), heat to 150°C, react for 8 hours, then cool to room temperature, filter and dry at 60°C for 5 hours to obtain Bi 2 GDj 3 SeI nanocrystals.
[0081] Step [3] Loading poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] on the surface of nickel foam substrate and assembling Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0082] c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent (the volume ratio between dimethyl sulfoxide and tetrahydrofuran is 1:1), 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi 2 GDj 3 SeI nanocrystals are added to the mixed solvent to form an additive solution (140 mL of 1-chloro-3-ethylbenzene, 20 g of dibenzoyl peroxide, and 20 g of Bi peroxide are added per liter of the additive solution). 2 GDj 3 The amount of SeI nanocrystals added was 70 g);
[0083] c2. Immerse the nickel foam in the N-mercapto-3-butyrylamide pyrrole product solution (the weight of the nickel foam immersed in each liter of the N-mercapto-3-butyrylamide pyrrole product solution is 110 g), immerse for 3 minutes at room temperature, then add a certain amount of the additive solution (the volume ratio between the additive solution and the N-mercapto-3-butyrylamide pyrrole product solution is 1:1), heat in a water bath to 70° C. and react for 8 hours to complete the loading of poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] and Bi on the surface of the nickel foam.2 GDj 3 The SeI crystals are assembled to finally obtain the photocatalytic degradation material.
[0084] Example 3
[0085] Preferred embodiment 3 of the present invention provides a method for preparing a photocatalytic degradation material for treating wastewater containing cefuroxime, comprising the following steps:
[0086] Step [1] synthesizing N-mercapto-3-butyrylaminopyrrole, specifically comprises the following operations:
[0087] Add mercaptopropionic acid and pyrrole to ethanol and mix to form a synthetic liquid A with a mercaptopropionic acid concentration of 100 mL / L and a pyrrole concentration of 220 mL / L; add butanamide and ferric chloride to deionized water and mix to form a synthetic liquid B with a butanamide concentration of 140 g / L and a ferric chloride concentration of 70 g / L; add a certain amount of synthetic liquid A to the synthetic liquid B (the volume ratio between the synthetic liquid A and the synthetic liquid B is 5:2), react at room temperature for 4 hours, and obtain an N-mercapto-3-butyrylamide pyrrole product solution.
[0088] Step [2] Preparation of Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0089] b1. Gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide were added to deionized water to form a reaction solution A having a gadolinium nitrate concentration of 50 g / L, a cerium trichloride concentration of 140 g / L, a tetrabutylammonium iodide concentration of 80 g / L and a sodium iodide concentration of 60 g / L; the mixture was stirred at room temperature for 5 hours until a solid phase was precipitated, the solid phase was filtered with filter paper, and dried at 40 ° C for 4 hours to obtain a GdSeOI precursor;
[0090] b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor into deionized water, mix to obtain reaction solution B (170 g of bismuth nitrate, 40 g of ammonium cerium nitrate and 230 g of GdSeOI precursor per liter of reaction solution B), heat to 120°C, react for 12 hours, then cool to room temperature, filter and dry at 40°C for 7 hours to obtain Bi 2 GDj 3 SeI nanocrystals.
[0091] Step [3] Loading poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] on the surface of nickel foam substrate and assembling Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0092] c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent (the volume ratio between dimethyl sulfoxide and tetrahydrofuran is 1:1), 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi 2 GDj 3 SeI nanocrystals are added to the mixed solvent to form an additive solution (190 mL of 1-chloro-3-ethylbenzene, 40 g of dibenzoyl peroxide, and 40 g of Bi peroxide are added per liter of the additive solution). 2 GDj 3 The amount of SeI nanocrystals added was 90 g);
[0093] c2. Immersing the nickel foam in the N-mercapto-3-butyrylamide pyrrole product solution (the weight of the nickel foam immersed in each liter of the N-mercapto-3-butyrylamide pyrrole product solution is 130 g), immersing for 10 minutes at room temperature, then adding a certain amount of the additive solution (the volume ratio between the additive solution and the N-mercapto-3-butyrylamide pyrrole product solution is 1:1), heating in a water bath to 50° C. and reacting for 12 hours to complete the loading of poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] and Bi on the surface of the nickel foam 2 GDj 3 The SeI crystals are assembled to finally obtain the photocatalytic degradation material.
[0094] Example 4
[0095] Preferred embodiment 4 of the present invention provides a method for preparing a photocatalytic degradation material for treating wastewater containing cephradine, comprising the following steps:
[0096] Step [1] synthesizing N-mercapto-3-butyrylaminopyrrole, specifically comprises the following operations:
[0097] Mercaptopropionic acid and pyrrole are added to ethanol and mixed to form a synthetic liquid A with a mercaptopropionic acid concentration of 90 mL / L and a pyrrole concentration of 205 mL / L; butyramide and ferric chloride are added to deionized water and mixed to form a synthetic liquid B with a butyramide concentration of 125 g / L and a ferric chloride concentration of 55 g / L; a certain amount of synthetic liquid A is added to the synthetic liquid B (the volume ratio between the synthetic liquid A and the synthetic liquid B is 3:2), and the mixture is reacted at room temperature for 5 hours to obtain an N-mercapto-3-butyramide pyrrole product solution.
[0098] Step [2] Preparation of Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0099] b1. Gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide were added to deionized water to form a reaction solution A having a gadolinium nitrate concentration of 70 g / L, a cerium trichloride concentration of 125 g / L, a tetrabutylammonium iodide concentration of 60 g / L and a sodium iodide concentration of 40 g / L; the mixture was stirred at room temperature for 6 hours until a solid phase was precipitated, the solid phase was filtered with filter paper, and dried at 50 ° C for 3.5 hours to obtain a GdSeOI precursor;
[0100] b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor into deionized water, mix to obtain reaction solution B (150 g of bismuth nitrate, 30 g of ammonium cerium nitrate and 220 g of GdSeOI precursor per liter of reaction solution B), heat to 135°C, react for 10 hours, then cool to room temperature, filter and dry at 50°C for 6 hours to obtain Bi 2 GDj 3 SeI nanocrystals.
[0101] Step [3] Loading poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] on the surface of nickel foam substrate and assembling Bi 2 GDj 3 SeI nanocrystals, specifically including the following operations:
[0102] c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent (the volume ratio between dimethyl sulfoxide and tetrahydrofuran is 1:1), 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi 2 GDj 3 SeI nanocrystals are added to the mixed solvent to form an additive solution (1-chloro-3-ethylbenzene is added in an amount of 165 mL, dibenzoyl peroxide is added in an amount of 30 g, and Bi is added in an amount of 100 g per liter of the additive solution). 2 GDj 3 The amount of SeI nanocrystals added was 80 g);
[0103] c2. Immersing the nickel foam in the N-mercapto-3-butyrylamide pyrrole product solution (the weight of the nickel foam immersed in each liter of the N-mercapto-3-butyrylamide pyrrole product solution is 120 g), immersing for 6 minutes at room temperature, then adding a certain amount of the additive solution (the volume ratio between the additive solution and the N-mercapto-3-butyrylamide pyrrole product solution is 1:1), heating to 60° C. in a water bath and reacting for 10 hours to complete the loading of poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] and Bi on the surface of the nickel foam 2 GDj 3 The SeI crystals are assembled to finally obtain the photocatalytic degradation material.
[0104] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a photocatalytic degradation material for treating wastewater containing cephradine, characterized in that: The following steps are included: Step [1] synthesizing N-mercapto-3-butyrylaminopyrrole; Step [2] preparing Bi2GdO3SeI nanocrystals; Step [3]: Loading poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] on the surface of the nickel foam substrate and assembling Bi2GdO3SeI nanocrystals.
2. The method for preparing a photocatalytic degradation material for treating wastewater containing cephradine according to claim 1, characterized in that: The step [1] specifically includes the following operations: Add mercaptopropionic acid and pyrrole into ethanol and mix to form a synthetic liquid A; add butanamide and ferric chloride into deionized water and mix to form a synthetic liquid B; add a certain amount of synthetic liquid A into the synthetic liquid B, react at room temperature for 4-6 hours, and obtain an N-mercapto-3-butyrylamide pyrrole product solution.
3. The method for preparing a photocatalytic degradation material for treating wastewater containing cephradine according to claim 2, characterized in that: The concentration of mercaptopropionic acid in the synthetic liquid A is 80 mL / L-100 mL / L, and the concentration of pyrrole is 190 mL / L-220 mL / L; the concentration of butanamide in the synthetic liquid B is 110 g / L-140 g / L, and the concentration of ferric chloride is 40 g / L-70 g / L; the volume ratio between the synthetic liquid A and the synthetic liquid B is 3-5:1-2.
4. The method for preparing a photocatalytic degradation material for treating wastewater containing cephradine according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Gadolinium nitrate, cerium trichloride, tetrabutylammonium iodide and sodium iodide were added to deionized water and mixed to form a reaction solution A; stirred at room temperature for 5 to 7 hours until a solid phase was precipitated, the solid phase was filtered with filter paper, and dried at 40-60 ° C for 3 to 4 hours to obtain a GdSeOI precursor; b2. Add bismuth nitrate, ammonium cerium nitrate and the GdSeOI precursor to deionized water, mix to obtain a reaction solution B, heat to 120-150°C, react for 8-12 hours, then cool to room temperature, filter and dry at 40-60°C for 5 to 7 hours to obtain Bi2GdO3SeI nanocrystals.
5. The method for preparing a photocatalytic degradation material for treating wastewater containing cephradine according to claim 4, characterized in that: In step b1, the concentration of gadolinium nitrate in reaction solution A is 50 g / L-90 g / L, the concentration of cerium trichloride is 110 g / L-140 g / L, the concentration of tetrabutylammonium iodide is 40 g / L-80 g / L, and the concentration of sodium iodide is 20 g / L-60 g / L.
6. The method for preparing a photocatalytic degradation material for treating wastewater containing cephradine according to claim 4, characterized in that: In step b2, the amount of bismuth nitrate added to each liter of reaction solution B is 130g-170g, the amount of ammonium cerium nitrate added is 20g-40g, and the amount of GdSeOI precursor added is 210g-230g.
7. The method for preparing a photocatalytic degradation material for treating wastewater containing cephradine according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. A certain amount of dimethyl sulfoxide and tetrahydrofuran are mixed to form a mixed solvent, 1-chloro-3-ethylbenzene, dibenzoyl peroxide and the Bi2GdO3SeI nanocrystals are added to the mixed solvent to form an additive solution; c2. Immerse the nickel foam in the N-mercapto-3-butyrylamide pyrrole product solution for 3-10 minutes at room temperature, then add a certain amount of the additive solution, heat it to 50-70°C in a water bath and react for 8-12 hours to complete the loading of poly [N-mercapto-3-butyrylamide pyrrole-2,5-di(p-methylphenylene)] and the assembly of Bi2GdO3SeI crystals on the surface of the nickel foam, and finally obtain the photocatalytic degradation material.
8. The method for preparing a photocatalytic degradation material for treating wastewater containing cephradine according to claim 7, characterized in that: In step c1, the volume ratio of dimethyl sulfoxide to tetrahydrofuran in the mixed solvent is 1:1; the amount of 1-chloro-3-ethylbenzene added per liter of the additive solution is 140mL-190mL, the amount of dibenzoyl peroxide added is 20g-40g, and the amount of Bi2GdO3SeI nanocrystals added is 70g-90g.
9. The method for preparing a photocatalytic degradation material for treating wastewater containing cephradine according to claim 8, characterized in that: In step c2, the weight of the nickel foam immersed in each liter of the N-mercapto-3-butyrylamide pyrrole product solution is 110-130 g; and the volume ratio between the additive liquid and the N-mercapto-3-butyrylamide pyrrole product solution is 1:1.